Evaluasi Implementasi Rekam Medis Elektronik terhadap Efisiensi Pelayanan Pasien di Puskesmas Kecamatan Pontianak Selatan, Kota Pontianak - Muhammad Fadhil Ramadhana; Dewi Kartika Lestari (Journal of Applied Health Sciences, 2026)
This study aimed to evaluate the implementation of Electronic Medical Records on patient service efficiency at the South Pontianak District Public Health Center, Pontianak City. Digital transformation in primary healthcare requires administrative systems that are fast, accurate, and integrated. This research employed a quantitative approach with an analytical cross sectional design. The sample consisted of 32 healthcare professionals using the system and 210 outpatients selected through systematic random sampling. Independent variables included system quality, information quality, and service quality based on the information systems success model. The dependent variable was service efficiency measured by registration waiting time, data retrieval time, clinical service duration, and documentation error rate. Data were analyzed using descriptive statistics and multiple linear regression. The results indicated that Electronic Medical Record implementation was categorized as good with a mean score of 4.12. Registration waiting time decreased by 39.1 percent, data retrieval time decreased by 63.1 percent, and total service time decreased by 29.9 percent compared to the manual system. Documentation errors declined from 12.3 percent to 4.1 percent. Regression analysis revealed that system quality and information quality significantly influenced service efficiency, explaining 61 percent of the variance. This study concludes that Electronic Medical Record implementation significantly improves patient service efficiency at the primary healthcare level. Strengthening technical support and enhancing human resource capacity are necessary to sustain optimal system performance.